1967
DOI: 10.1149/1.2426708
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Aluminum in Aqueous Chloride Solutions

Abstract: By using a high‐speed technique described in ref. (1), anodic (aluminum dissolution) polarization data have been obtained for aluminum surfaces free from oxide films and from the normal concurrent hydrogen evolution. Similarly cathodic (hydrogen evolution) polarization data have been produced for oxide‐free aluminum surfaces on which the usual simultaneous anodic process has been suppressed. These results have been applied to the interpretation of the static “mixed” potential reported in ref. (1). It has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1978
1978
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…The OCP drop at the beginning of the test could be linked to the dissolution of the protective oxide [27]. Importantly, Hagyard et al showed that the potential rose to a peak at the beginning of the immersion and that this increase was attributed to the dissolution of aluminum and to the formation of the protective oxide [28,29]. This reaction was very quick and, thus, is rarely observed, which was the case in this study because no peak was visible in Fig.…”
Section: Corrosion Susceptibility Of the 2050 Alloy During Continuous Immersion Testsmentioning
confidence: 49%
“…The OCP drop at the beginning of the test could be linked to the dissolution of the protective oxide [27]. Importantly, Hagyard et al showed that the potential rose to a peak at the beginning of the immersion and that this increase was attributed to the dissolution of aluminum and to the formation of the protective oxide [28,29]. This reaction was very quick and, thus, is rarely observed, which was the case in this study because no peak was visible in Fig.…”
Section: Corrosion Susceptibility Of the 2050 Alloy During Continuous Immersion Testsmentioning
confidence: 49%
“…In the present investigation, the presence of Al(OH) 3 illustrated the hydration of Al 2 O 3 and formation of Al(OH) 3 during the salt spray test. The binding energy of Cl 1 s was approximately 199.3 eV, corresponding to corrosion products after fretted in NaCl, and it was believed that Al(OH)Cl X was produced in SST after the sample immersed in salt fog for long time 41 . The obtained at.% of chlorine on SAOF and PAOF were about 4% and 23%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…While both scratch repassivation current and potential transients have been used by previous investigators to understand passivity for many years, [31] previous work was concerned primarily with producing data for modeling stress corrosion cracking or corrosion fatigue crack propagation rates or for comparing the pitting behavior of alloys. [20,21,[32][33][34][35] This is the first time that these two types of experiments have been used together to compare the anodic and cathode rate-limiting conditions for fatigue cracks in two alloys. Even though no significant difference was revealed by these tests, ruling out any contribution of a difference in repassivation rates was a significant result that dramatically reduces ambiguity in the conclusions of this study.…”
Section: A Failure Mechanismmentioning
confidence: 99%